EXPERIMENTAL STUDY OF DRYING BY THE SOLARIUM VARIABLE BAFFLE SENSOR OF YELLOW AND GREEN LEMON TO KEEP THESE VITAMINS FOR A LASTING AND NATURAL MEDICINAL THERAPY - Abderrahmane, Abene; Eddine Seddiki, Mohamed Salah; Mohamed Si Youcef, Aurora Morocini (International Journal of Research -GRANTHAALAYAH, 2018)
The use of variable baffle solar panels for drying is the low level of heat exchange with the air in the dynamic vein of the solar panel. This weakness in such systems does not provide optimal performance or high thermal efficiency from their use. There is, however, a very noticeable improvement in heat transfer when the baffles are placed in rows in the ducts. To conduct the experiments, solar energy was simulated, the goal being to improve the relationship between temperature and thermal efficiency of a solar panel air heating plane and to use the system to reduce the time to gently dry the lemon to keep these vitamins. lemon and destinine for a sustainable therapy (the lemon promotes the absorption of calcium and in case of rhumet gill or five also to treat sinusitis, against migraine solair dryness and also for sustainable conservation and also for a sustainable medicine for a sustainable medicine.